2020
DOI: 10.1002/lt.25731
|View full text |Cite
|
Sign up to set email alerts
|

Role of Molecular Biomarkers in Liver Transplantation for Hepatocellular Carcinoma

Abstract: Patient selection and organ allocation for liver transplantation (LT) in patients with hepatocellular carcinoma (HCC) relies predominantly on clinical parameters, such as tumor burden (ie, radiological imaging). Patients transplanted withinMilan criteria have outstanding outcomes with a 5-and 10-year survival of 70% and 55%, respectively. Tumor recurrence after transplantion is rare in these patients (10%); however, treatment options upon recurrence are generally limited, and outcomes are poor. There are also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 61 publications
(91 reference statements)
0
30
0
2
Order By: Relevance
“…Over the last decade, we have significantly improved our understanding of the molecular landscape of HCC [42]. Numerous studies have investigated the utility of molecular biomarkers, such as DNA alterations, to predict outcomes in patients following LT for HCC [42]. Circulating miRNA has emerged as one of the most attractive tools for the early diagnosis of cancers [42][43][44].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Over the last decade, we have significantly improved our understanding of the molecular landscape of HCC [42]. Numerous studies have investigated the utility of molecular biomarkers, such as DNA alterations, to predict outcomes in patients following LT for HCC [42]. Circulating miRNA has emerged as one of the most attractive tools for the early diagnosis of cancers [42][43][44].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have investigated the utility of molecular biomarkers, such as DNA alterations, to predict outcomes in patients following LT for HCC [42]. Circulating miRNA has emerged as one of the most attractive tools for the early diagnosis of cancers [42][43][44]. Some authors have reported that miRNA markers were useful predictors of HCC recurrence after LT [42,[45][46][47].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The approaches employed to treat illness by gene therapy consist of gene replacement, gene restoration, gene extension, gene muzzling, vaccination, and, currently, gene-editing technology (Alsaggar and Liu, 2016;Chew et al, 2016;Karimian et al, 2019). Thus, the identification of a gene that can be used as a potential biomarker is an important step in the treatment of liver cancer (West et al, 2019;Zheng et al, 2019;Lu et al, 2020;von Felden and Villanueva, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Hepatocellular carcinoma (HCC) is one of the most frequent reasons of human abdominal malignancies-associated mortality worldwide (1). As the most prevalent kind of primary liver cancers, HCC accounts for over 70% of liver carcinomas(2), with its incidence increasing over the past several decades (3), which essentially results from hepatitis, alcohol abuse and several metabolic syndromes (4). The present tactics to HCC consist of radical treatments such as curative resection, liver transplantation for local lesions (5), and palliative therapies including ablation, chemotherapy et cetera (6).…”
Section: Introductionmentioning
confidence: 99%